Analysis of the Application of PSAK No.16 to Fixed Asset Accounting at PT. PLN Nusantara Power - Umiah, Riza; Rahmazaniati, Linda (Institut Bisnis dan Informatika Kesatuan, 2023)
Fixed assets are one of the main aspects of the company's wealth with a large value which plays a role in providing and smoothing the company's operations and is expected to provide economic benefits in the long term. The purpose of this research is to determine the extent to which the company has implemented fixed asset accounting treatment in accordance with Statement of Financial Accounting Standards (Pernyataan Standar Akuntansi Keuangan/PSAK) No. 16 in the sustainability of company activities. The problem that occurs is the pricing policy for the acquisition of fixed assets, depreciation of fixed assets, treatment of recognition after acquisition of fixed assets, disposal and disclosure of fixed assets in the financial statements. The method used in this research is a qualitative method. This research highlights the importance of implementing PSAK No.16 to improve entity performance and compliance in recording and depreciating assets so as to improve accounting standards, and contribute to the development of accounting standards in updating or improving PSAK No.16. Thus, entities can manage their assets efficiently. The research results concluded that the company had carried out accounting activities based on the company's accounting policies which had led to the Statement of Financial Accounting Standards.